Question

21. \( (3 c-8)^{2} \)

Ask by Barrett Montgomery. in the United States
Jan 30,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( 9c^{2} - 48c + 64 \)

Solution

To expand the expression \( (3c - 8)^2 \), you can use the formula for squaring a binomial: \[ (a - b)^2 = a^2 - 2ab + b^2 \] Applying this formula to \( (3c - 8)^2 \): \[ (3c - 8)^2 = (3c)^2 - 2 \times 3c \times 8 + 8^2 \] Calculate each term: 1. **First term:** \((3c)^2 = 9c^2\) 2. **Second term:** \(-2 \times 3c \times 8 = -48c\) 3. **Third term:** \(8^2 = 64\) Combine these results: \[ (3c - 8)^2 = 9c^2 - 48c + 64 \] **Final Answer:** \( 9c^{2} - 48c + 64 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To expand \( (3c - 8)^{2} \), we use the binomial formula \((a - b)^{2} = a^{2} - 2ab + b^{2}\). Here, \(a = 3c\) and \(b = 8\). So, we get: - First term: \((3c)^{2} = 9c^{2}\) - Second term: \(-2(3c)(8) = -48c\) - Third term: \(8^{2} = 64\) Putting it all together, the expansion gives us: \[ (3c - 8)^{2} = 9c^{2} - 48c + 64 \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy